Cover Picture: A Biocatalytic Nanomaterial for the Label‐Free Detection of Virus‐Like Particles (ChemBioChem 11/2017). (15th May 2017) - Sykora, Sabine; Correro, M. Rita; Moridi, Negar; Belliot, Gaël; Pothier, Pierre; Dudal, Yves; Corvini, Philippe F.‐X.; Shahgaldian, Patrick
Abstract : The cover picture shows a novel synthetic nanomaterial capable of specific biomolecular detection using an internal biocatalytic colorimetric detection and amplification system. The design of this nanomaterial relies on the ability to accurately grow hybrid protein–organosilica layers at the surface of silica nanoparticles, with a precision down to the nanometer scale. The first layer covering the core silica nanoparticle consists of an immobilized enzyme in a soft organosilica shell. This layer is further covered with a virus‐recognition layer produced through virus imprinting. The enzyme substrate can freely diffuse to the enzyme active site through empty imprints. In a virus‐binding assay, the presence of the target virus in the imprints prevents the diffusion of the substrate to the enzyme active site; this results in spectrophotometrically measurable enzyme inhibition. The method allows label‐free detection and quantification of viruses at picomolar concentrations. More information can be found in the communication by P. Shahgaldian et al. onpage 1001 in Issue 11, 2017 (DOI:10.1002/cbic.201700126 ).